The Role of Immune and Inflammatory Cells in Idiopathic Pulmonary Fibrosis - Desai, Omkar; Winkler, Julia; Minasyan, Maksym; Herzog, Erica L. (Frontiers in Medicine, 2018)
The contribution of the immune system to Idiopathic Pulmonary Fibrosis (IPF) remains poorly understood. While most sources agree that IPF does not result from a primary immunopathogenic mechanism, evidence gleaned from animal modeling and human studies suggests that innate and adaptive immune processes can orchestrate existing fibrotic responses. This review will synthesize the available data regarding the complex role of professional immune cells in IPF. The role of innate immune populations such as monocytes, macrophages, myeloid suppressor cells, and innate lymphoid cells will be discussed, as will the activation of these cells via pathogen associated molecular patterns derived from invading or commensural microbes, and danger associated molecular patterns derived from injured cells and tissues. The contribution of adaptive immune responses driven by T-helper cells and B cells will be reviewed as well. Each form of immune activation will be discussed in the context of its relationship to environmental and genetic factors, disease outcomes, and potential therapies. We conclude with discussion of unanswered questions and opportunities for future study in this area.